Chemical Constituents and Toxicity Screening of Three Aromatic Plant Species from Peninsular Malaysia - Siti Rahimah, Jumaat; Saiful Nizam, Tajuddin; Runglawan, Sudmoon; Arunrat, Chaveerach; Ummi Hani, Abdullah; Rozi, Mohamed (North Carolina State University, 2017)
Medicinal and aromatic plants (MAPs) are widely valued for their aromas, tastes, and treatments for various human illnesses. The chemical constituents and toxicity content of three aromatic plant species, Syzygium polyanthum Wight (Walp.), Monocarpia marginalis (Scheff.) J. Sinclair, and Chromolaena odorata (L.) R.M. King & H. Rob, were determined, via gas chromatography (GC) with mass spectrometry (MS), and flame ionization detector (FID). Altogether, 116 compounds were identified in the essential oils and hexane and methanol extracts. Toxicity evaluations were carried out on human peripheral blood mononuclear cells (PBMCs). Three plant samples were found toxic to human PBMCs. The essential oils of M. marginalis and C. odorata, and the hexane extract of C. odorata yielded IC50 and LD50 values of 76 mg/mL and 6,913 mg/kg, 14 mg/mL and 3,684 mg/kg, and 2.45 mg/mL and 1,927 mg/kg, respectively. Based on the LD50 values, M. marginalis and C. odorata can be classified as slightly and moderately hazardous, respectively. A detailed toxicity evaluation via comet assay showed that M. marginalis and C. odorata induced significant DNA damage (p < 0.05). As for S. polyanthum, the species did not give any cytotoxic or genotoxic evidences.